Plant functional assembly is mediated by rainfall and soil conditions in a seasonally dry tropical forest - Pinho, Bruno X.; Tabarelli, Marcelo; Engelbrecht, Bettina M.J.; Sfair, Júlia; Melo, Felipe P.L. (Basic and applied ecology, 2019)
Understanding how species assembly is influenced by the interplay of climate, local environmental conditions and human-caused disturbances remains a central question in ecology and conservation. Here, we assess how plant species abundance is determined by combinations of functional traits (ecological strategies) and interacting gradients of rainfall, soil conditions (fertility and field capacity) and chronic anthropogenic disturbance in a Caatinga dry tropical forest, Brazil. We tested for trait–environment relationships using multivariate methods (RLQ) accounting for groups of species sharing similar responses to gradients and similar expression of multiple traits (i.e. response groups). Overall, species’ abundances changed predictably in response to rainfall and soil fertility, and were mediated by functional traits, i.e. species with particular trait combinations tended to respond similarly to multifactorial conditions. Briefly, three ecological strategies emerged: species with low wood density and soft (i.e. lower dry matter content), thick leaves converged into a trait syndrome characterizing a drought-avoidance strategy through water storage. They were particularly abundant under extremely low precipitation and relatively high soil field capacity. Under conditions of increasing rainfall and decreasing soil field capacity, species with high wood density were favored, consistent with a drought-tolerance strategy. However, these species fell into two groups relative to leaf-investment: more conservative leaves (low SLA) on relatively fertile soils vs. thinner and softer (i.e. high SLA) leaves on unfertile soils. In seasonally dry tropical forests, low SLA on relatively fertile soils may represent a water conservation strategy. Unexpectedly, no ecological strategy emerged in response to disturbance. The patterns we uncovered help to understand the interplay between precipitation, soil fertility and anthropogenic disturbance in plant species filtering in seasonally dry tropical forests. Moreover, our results underline that impacts of future climate change will depend on how rainfall patterns covary with finer-scale environmental factors such as soil fertility and field capacity.